Analisis Penerapan Etika Bisnis Islam dalam Membangun Loyalitas Konsumen (Studi Kasus Kafe Cavelet) - Sulastri, Ratu; Syihabudin; Fakhrudin, Muhamad (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
The purpose of this research is to describe in detail about Islamic business ethics in building consumer loyalty at Cavelet Cafe. This research is located on jl. Palka cipelem, paleh kec. Pabuaran kab. Serang prov. Banten. Researchers took samples and data through interviews with the owner, employees, and consumers of this Cavelet cafe. In this study the total number of informants was 2 people. The data validity test technique used is the trigulation technique. While the data analysis technique used is a qualitative data analysis technique consisting of data reduction, data presentation, and conclusions. The results of this study indicate that the Islamic business practices carried out by Cavelet Cafe have been carried out according to Islamic business activities based on Islamic business ethics. However, this cavelet cafe has not fully implemented indicators of building good relationships with consumers and ihsan or benevolence in serving consumers. The implementation of the principles of Islamic business ethics in increasing customer loyalty has been implemented quite well although there are still shortcomings in one of the principles. The level of consumer loyalty at Cavelet Cafe as a whole is good, but there are still some consumers who state that it is not good for consumers, so consumers are reluctant to make repeat purchases and recommendations to prospective buyers or other buyers. Keywords: Islamic Business Ethics; Consumer Loyalty